Research on Dynamic Characteristics of Oil and Gas Suspension Cylinder. (March 2019) - Sha, Lin; Zhang, Hang; Chen, Gang
Abstract: Aiming at the complex dynamic characteristics of oil and gas suspension cylinders, the simulation model of oil and gas suspension cylinder is established based on AMESim software, and the model is used to simulate the oil and gas suspension cylinder. The main factor in the output characteristics of the cylinder hanging paper focuses on the impact analysis of changes in the characteristics of the nonlinear stiffness characteristics and damping characteristics of the suspension cylinders.